Hospital Antibiotic Stewardship Programs - Qualitative analysis of numerous hospitals in a developing country - Madiha Mushtaque; Farah Khalid; Azfar Ather Ishaqui; Rida Masood; Muhammad Bilal Maqsood; Iyad Naeem Muhammad (Elsevier, 2019)
Summary: Antimicrobial stewardship programs (ASP) are an essential practice to prevent increasing resistance against antibiotics. A successful ASP monitors not only prescribing patterns and practices but also contributes in minimizing the toxic effects of antibiotics. Moreover, ASP also facilitates the selection of disease specific antibiotics and enforces rules and regulations to rationalize the use of antibiotics. The aim of the study is to highlight the core elements of Hospital Antibiotic Stewardship Programs in Karachi. The key elements proposed by center of disease control (CDC) such as; leadership, accountability, drug expertise, actions to support optimal antibiotic use, tracking (monitoring antibiotic prescribing, use and resistance), reporting information to staff on improving antibiotic use and resistance and education were evaluated on Yes/No scale. The data was collected from 44 hospitals of different categories in Karachi and all the major elements were studied. It was observed that all the hospitals in one setting failed to comply with all the guidelines. It has been concluded that efforts should be made to design ASP at each hospital and implemented through suitable policies and procedures. Keywords: Antibiotic, Hospital, Stewardship, CDC, Resistance